Molecular Logic as a Means to Assess Therapeutic Antidotes - Unger-Angel, Linor; Motiei, Leila; Margulies, David (Frontiers in Chemistry, 2019)
An emerging direction in the area of molecular logic and computation is developing molecular-scale devices that can operate in complex biological environments, such as within living cells, which are beyond the reach of conventional electronic devices. Herein we demonstrate, at the proof-of-principle level, how concepts applied in the field of molecular logic gates can be used to convert a simple fluorescent switch (YES gate) that lights up in the presence of glutathione s-transferase (GST), into a medicinally relevant INHIBIT gate that responds to both GST and beta-cyclodextrin (β-CD) as input signals. We show that the optical responses generated by this device indicate the ability to use it as an enzyme inhibitor and, more importantly, the ability to use β-CD as an ‘antidote’ that prevents GST inhibition. The relevance of this system to biomedical applications is demonstrated by using the INHIBIT gate and β-CD to regulate the growth of breast cancer cells, highlighting the possibility of applying supramolecular inputs, commonly used to control the fluorescence of molecular logic gates, as antidotes that reverse the toxic effect of chemotherapy agents. We also show that the effect of β-CD can be prevented by introducing 1-adamantecarboxylic acid (Ad-COOH) as an additional input signal, indicating the potential of obtaining precise, temporal control over enzyme activity and anticancer drug function.